A Study of the Prevalence of Cytotoxic and Non-Cytotoxic Klebsiella oxytoca Fecal Colonization in Two Patient Populations. Issue 4 (2009) - Smith, Stephen A; Campbell, Sarah J; Webster, Duncan; Curley, Michael; Leddin, Desmond; Forward, Kevin R
Abstract : BACKGROUND: Klebsiella oxytoca is a cause of antibiotic-associated hemorrhagic colitis. Few reports of the occurrence of K oxytoca within stool exist and there is no gold standard method for its isolation. METHODS: MacConkey agar was modified to culture K oxytoca . Ampicillin was added and adonitol was substituted for lactose. Rectal swabs from 200 patients being screened for vancomycin-resistant enterococci (VRE) and stool specimens from 429 patients who tested negative for Clostridium difficile cytotoxin were cultured. K oxytoca isolates were evaluated for cytotoxicity to HEp-2 cells. Available charts of K oxytoca -positive patients and a convenience sample of 93 K oxytoca -negative patients who underwent testing for C difficile cytotoxicity were reviewed retrospectively for documentation of bloody stool. RESULTS: K oxytoca was isolated from 14 of 200 patients (7.0%) being screened for VRE; only one of the 14 isolates (7.1%) was cytotoxic. The organism was isolated from 42 of 429 patients (9.8%) tested for C difficile cytotoxicity; 10 isolates (23.8%) were cytotoxic. Differences in isolation and cytotoxicity rates between groups were not statistically significant. Two of 13 (15.4%) K oxytoca -positive patients screened for VRE, three of 27 (11.1%) K oxytoca -positive patients tested for C difficile cytotoxicity, and 11 of 93 (11.8%) patients from the convenience sample had documented bloody stool. CONCLUSIONS: A medium that greatly facilitates isolation of K oxytoca was developed. Occurrence of K oxytoca colonization was similar in the two patient populations studied and isolation of cytotoxic K oxytoca was not usually associated with hematochezia. Current understanding of the occurrence and causality of antibiotic-associated hemorrhagic colitis is insufficient for clinical laboratories to begin culturing K oxytoca and testing for cytotoxicity.